Modification in Webster technique for lower lip reconstruction, using bilateral nasolabial flaps to improve reconstruction of vermilion - Victor Vieira Orsi; Antônio Carlos Pinto Oliveira; Daniel Sperb; David Sena; Jefferson Braga Silva; Marcus Vinícius Martins Collares; Nilton Tabajara Herter (Revista Brasileira de Cirurgia Plástica, 2016)
INTRODUCTION: Many authors consider the Bernard technique modified by Webster the first choice for total lower lip reconstruction. This technique preserves skin folds and anatomical landmarks on the face, and interferes minimally with the tactile sensibility of the reconstructed lip, resulting in satisfying cosmetic and functional outcomes. Despite agreeing with the principles of the Webster technique, a modification is proposed to improve reconstruction of vermilion, by using bilateral nasolabial flaps associated with the original advancement flaps. METHODS: We report five surgical cases carried out between 2003 and 2008, and discussion of results. RESULTS: Dissection need to advance flaps in Bernard-Webster technique does not make nasolabial flaps unviable, and they can be rotated properly to add volume and skin to the reconstructed vermilion. CONCLUSION: Proposed modification of Bernard-Webster technique does not increase risk or damage compared with classic technique, and it maintains the same reconstructive capabilities or even enhances it.